ASPEK HUKUM GADAI (RAHN) DALAM PERSPEKTIF HUKUM ISLAM - Bustanul Arifin; Moh. Ulumuddіn (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
Abstract: Background. Fiduciaryis one of the financing products available in financial institutions, where this financing agreement aims to make it easier for customers to obtain loans by fiduciary gold or other valuables that have resale value such as: land certificates or other building documents, Proof of Motor Vehicle Ownership (BPKB), and Employee Decree (SK), as collateral for the proposed loan and proof that he is able to make repayment at the agreed time. For this reason, in this practice the researcher will describe aspects of pawn law from an Islamic legal perspective. Methods. in this research, emphasizing the legal aspect of fiduciary, this research takes the form of library research (library), with data collection techniques through tracing major theories in literature studies related to fiduciary from an Islamic perspective. The analysis technique used is descriptive analysis, this technique begins by describing the data related to the pawn, then sorting it according to research needs, this pattern will be carried out repeatedly, to ensure the data obtained is in accordance with the research focus Results. Aspects of fiduciary law in an Islamic perspective include the basis for enforcement which is in accordance with Islamic principles, the pillars and conditions of fiduciary, control of collateral goods, binding of collateral goods, use of collateral goods, sale of collateral goods, destruction of collateral goods and expiry of collateral goods. In general, these legal aspects are stated in Islamic law in detail.